EFFORTS TO IMPROVE STUDENTS' CHARACTER THROUGH EXTRACURRICULAR ACTIVITIES FOR GRADE 5 ELEMENTARY - Diah Nur Azizah; Febrina Dafit (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe in depth the contribution of extracurricular activities of dance, pencak silat, and futsal in shaping the character of 5th grade students of SDN 42 Pekanbaru. The main focus of this research is on the aspects of discipline, responsibility, and confidence. Using a descriptive qualitative approach, data was collected through participatory observation, in-depth interviews with students and teachers, and documentation studies. The results of the study show that regular and consistent participation in extracurricular activities has proven to be effective in fostering student discipline. This can be seen from the students' adherence to a regular training schedule, obedience to the rules set by the coach, and their commitment to completing the tasks or responsibilities given. Furthermore, this extracurricular also plays a significant role in shaping the character of responsibility. Students learn to carry out their roles, both as individuals and as part of a team, and they also begin to understand and accept the consequences of every action or decision they take. In addition, extracurriculars have a positive impact on increasing student confidence. This confidence grows through the mastery of new skills that they gradually practice, the courage to perform or compete in public, and an unyielding attitude in the face of difficulties during the training process. However, it was found that the development of this character was not completely even among all students. This study concludes that extracurricular activities, if systematically integrated with the school curriculum, can be a very effective and essential strategy in character education at the elementary school level.